278 Effect of Feeding CARS on Digestibility in Finishing Cattle Diets. (7th May 2021) - Gibbons, John; Watson, Andrea K; Erickson, Galen E; Spore, Tyler; Wilson, Hannah; Wilson, Jonathan W; Butterfield, Kylie
Abstract: An experiment was conducted to evaluate the digestibility of a novel liquid feed, Condensed Algal Residue Solubles (Veramaris, Blair, NE) in finishing cattle diets. Mass production of algae to harvest omega-3 fatty acids results in byproduct production of CARS (25.4% DM, 19.3% CP, 8.3% Fat, 9.96% Na on DM basis), made up of the de-oiled algae cells and residual fermentation substrates. The CARS product has generally recognized as safe (GRAS) status. Six ruminally and duodenally cannulated crossbred steers were assigned randomly to 1 of 3 treatments over 3 collection periods, for a 3 x 3 replicated Latin Square design. Treatments differed by increasing inclusion of CARS (0, 2.5, and 5% of diet DM) fed with CARS replacing steam flaked corn (72, 69.5, and 67% of diet DM as CARS inclusion increased). All diets contained 15% dry distillers grains, 8% alfalfa haylage, and 5% supplement. Cattle were dosed with 10 g of titanium dioxide per day. Duodenal and fecal samples were collected four times per day across four days and composited by period for each animal. Fecal samples were analyzed for titanium dioxide concentration to determine fecal output and diet digestibility. Data were analyzed with CARS inclusion and period as fixed effects and animal as a random effect. Orthogonal contrasts were used to test linear and quadratic effects of CARS inclusion. There were no significant differences for DM intake and OM intake between the different CARS inclusions (P ≥ 0.17), averaging 7.76 kg DM/d and 6.94 kg OM/d. Total tract DM digestibility was not affected by treatment (P ≥ 0.71) and averaged 73.0%. Total tract OM digestibility was also not different between treatments (P ≥ 0.93) and averaged 71.1%. Replacing steam flaked corn with CARS up to 5% of diet DM in finishing cattle diets did not affect diet digestibility.